Leadership Coordination: The Key to Mediating the Influence of Leadership and Organizational Structure on Work Performance - Setiawati, Erlina; Sutisna; Sari, Gema Ika (Jurnal Economic Resource, 2025)
Employee performance is a key indicator of the effectiveness of public organizations. At the Banten Provincial DPRD Secretariat, low administrative performance, weak discipline, and ineffective organizational coordination are still found, necessitating research into the factors influencing employee performance. This study aims to analyse the influence of leadership style and organizational structure on employee work performance, as well as the role of leadership coordination as a mediator in this relationship. The method used was quantitative with an explanatory design. The study population included all employees of the Banten Provincial DPRD Secretariat, with a sample of 271 people determined using the Slovin method. Data were collected using a questionnaire that had been tested for validity and reliability, then analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The results of the study indicate that leadership style and organizational structure have a significant positive influence on work performance, and both contribute significantly to leadership coordination. Leadership coordination has been shown to mediate the relationship between leadership style and organizational structure on employee work performance. In conclusion, the effectiveness of leadership and organizational structure in improving work performance is highly dependent on established coordination. These findings enrich the literature on performance management and motivation and can serve as a basis for developing personnel policies at the Banten Provincial DPRD Secretariat.